2002
DOI: 10.2337/diacare.25.11.2058
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Rosiglitazone and Glyburide on Cardiovascular Function and Glycemic Control in Patients With Type 2 Diabetes

Abstract: A total of 52 weeks of therapy with RSG (4 mg b.i.d.) did not adversely affect cardiac structure or function in patients with type 2 diabetes and produced significant and sustained reductions in hyperglycemia. Decreases in ambulatory diastolic blood pressure with RSG were superior to those with GLB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
110
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 244 publications
(116 citation statements)
references
References 23 publications
4
110
0
2
Order By: Relevance
“…The effect of rosiglitazone therapy on LV mass has been studied in experimental and clinical setting, however revealing controversial results [13-17]. Evidence from experimental studies has shown that administration of thiazolidinediones might be associated with the development of LV hypertrophy [14,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of rosiglitazone therapy on LV mass has been studied in experimental and clinical setting, however revealing controversial results [13-17]. Evidence from experimental studies has shown that administration of thiazolidinediones might be associated with the development of LV hypertrophy [14,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, only few studies have evaluated the possible hypertrophic effect of thiazolidinediones in patients [15,17]. St. John Sutton et al [17] studied patients with type 2 diabetes using echocardiography and demonstrated that long-term use of rosiglitazone is not associated with increase in LV mass (or functional impairment).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations